Reducing susceptibility to drought under growing conditions as set by farmers: The impact of new generation drought tolerant maize varieties in Uganda - Habte, Endeshaw; Marenya, Paswel Phiri; Beyene, Fekadu; Bekele, Adam (Frontiers Media, 2023)
Given the challenges brought about by the increasing frequency of climatic stressors (droughts) and other biotic challenges (pests and diseases), breeding for tolerance to these traits is now seen as an indispensable adjunct to the enhancement of yield potential. Drought tolerant (DT) maize varieties that do well under moderate drought and outperform (or do not underperform) commercial checks under normal rainfall are becoming available. This study examines the role of these maize varieties in mitigating the effects of drought on maize yields in drought-prone areas of eastern Uganda. We estimate the causal impact of these new generations of maize varieties using a multinomial endogenous switching regression treatment effect framework. The average treatment effects of adopting DT maize show that farmers who actually cultivated DT maize achieve 30% more yield than what they would have obtained with non-DT hybrids. Similarly, average treatment effects on the untreated, revealed that farmers who grew non-DT modern and local maize would have 32 and 54% more yield, respectively, if they instead had adopted DT maize. While being superior to all other maize seeds, the magnitudes of the benefits of DT maize varieties were more pronounced in areas with comparatively less rainfall amount providing strong evidence that the yield potential of these varieties is stable across space and a wide range of rainfall conditions. If the genetic gains of these varieties can be secured over the long term, their impacts in improving the resilience of maize farming systems are likely to be considerably large and favorable.